LUXURY HOSPITALITY SERVICE ADOPTION AMONGST INDIAN MILLENNIAL: AN ANALYTICAL APPROACH - Sudhanshu Gupta; Pavinder Kour (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2021)
Understanding the Indian millennial travelers is vital in providing insights into their behavior while presenting additional challenges to successfully targeting different demographic cohorts for luxury products and services. The present study investigates the factors that define the value perceptions and attitude of Millennials towards luxury service consumption in India. The findings revealed social value as an important factor that influences the attitude of millennial consumers towards purchasing luxury tourism services. Along with providing a theoretical model for behavior, the study provides insights into measuring tourist value preferences by utilizing empirical data within luxury tourism contexts and suggests the tourism and hospitality business practitioners to make innovations in product, service management, and marketing to draw the attention of such a potential segment. Moreover, this study augments the existing knowledge of luxury value and travel patterns of emerging and potential consumers while developing a theoretical model to validate and analyze the luxury service consumption amongst them.